The formation of character in the writings of Ellen G. White: a perspective of holistic education - Martinez Tejada, Victoria (2019)
The study of character is a subject that is relevant for Adventist educators, because from now on it is the subject in which the curriculum guidelines of the various educational training programs are developed and constructed at the levels of formation. In order to have a clear direction regarding the character and its scope and implications, it is important to develop a qualitative approach research study, with a juxtaposed design of emergent and narrative based theory, to know the thoughts of Ellen G. White with regard to this topic and its evolution throughout her prophetic ministry (1844 - 1915). The Seventh-day Adventist Church (SDA) considers that Ellen G. White is a prophet of God and her writings are considered as authoritative for the diverse guidelines of the work of the church and its parishioners.